Methods of gadoid fish species identification in food and their economic impact in the Czech Republic: a review - Z. Hubalkova; P. Kralik; B. Tremlova; E. Rencova (Veterinární Medicína, 2007)
The purpose of the present study was to give an overview of imported and traded gadoid fish species (Gadiformes) in the Czech Republic and to describe available methods for their authentication. Due to the increasing interest of customers in the purchase of buy fish meat and other seafood animals, it is necessary to have available analytical methods with discriminating power of respective fish species. With regard to different values and prices of various fish species, these may be adultered. Until recently, electrophoretic, chromatographic and immunological methods based on the analysis of proteins extracted from fish musculature seemed to be promising. Using these methods, various fish species can be identified in fresh, chilled and frozen products. However, they often fail in heat treated products. Molecular biology methods based on DNA analysis are more reliable and suitable for the analysis of fish products that have been heat treated during the production process.